Respuesta :

Answer:

[tex]6x-11[/tex]

Step-by-step explanation:

Factor the numerator  [tex]36x^2-121[/tex]:

[tex]\implies 36x^2-121=(6x+11)(6x-11)[/tex]

Therefore,

[tex]\dfrac{36x^2-121}{6x+11}=\dfrac{(6x+11)(6x-11)}{6x+11}[/tex]

Cancel the common factor [tex](6x + 11)[/tex]:

[tex]\implies\dfrac{(6x+11)(6x-11)}{6x+11}=6x-11[/tex]

Therefore,

[tex]\dfrac{36x^2-121}{6x+11}=6x-11[/tex]

  • 36x²-121/6x+11
  • (6x)²-(11)²/6x+11

(a+b)(a-b)=a²-b²

  • (6x+11)(6x-11)/6x+11

Cancel 6x+11

  • 6x-11